Nucleosomal structure of sea urchin and starfish sperm chromatin. Histone H2B is possibly involved in determining the length of linker DNA. - Zalenskaya, I A (1981)
Comparison has been made between sea urchin and starfish sperm chromatin. The only protein by which chromatins from these sources differ significantly is histone H2B. Sea urchin sperm H2B is known to contain an elongated N-terminal region enriched in Arg. Analysis of the micrococcal nuclease digests of sea urchin and starfish nuclei in one- and two-dimensional electrophoresis has shown that sperm chromatin of both animals consists of repeated units similar in general features to those of rat thymus or liver. However, DNA repeat length in chromatin of sea urchin sperm (237 bp) is higher than that of starfish sperm (224 bp), while the core DNA length does not differ and is the same as in the chromatin of rat liver or thymus. A suggestion has been made that the N-terminal region of histone H2B is associated with the linker DNA and is responsible for the increased length of sea urchin linker DNA.